Identification of the tetraspanin gene family in sugarcane and its response to sugarcane mosaic virus infection - Cui, Zhiyuan; Li, Yifei; Zeng, Kang; Yang, Zongtao; Yu, Quanxin; Liu, Haoming; Zhan, Zhenhe; Zhang, Hai; Huang, Guoqiang; Xu, Jingsheng (Frontiers in Plant Science, 2025)
IntroductionSugarcane mosaic virus (SCMV, Potyvirus) causes mosaic diseases and seriously threatens sugarcane production. Potyviral 6K2 protein plays a key role in viral infections. We previously screened a tetraspanin (TET)-like protein that interacts with SCMV-6K2 from a sugarcane cDNA yeast library. Although TETs have been extensively studied in response to viral infections in animals, the TET gene family in sugarcane and its role in SCMV infections remain largely unknown. This study aimed to identify the TET genes in sugarcane and determine their response to SCMV infection.MethodsWe employed genome-wide identification, phylogenetic analysis, real-time quantitative PCR (RT-qPCR), subcellular localization, and multiple protein–protein interaction assays to characterize TETs and their interactions with viral 6K2 proteins.ResultsWe identified 35, 113, 73, and 17 TETs in the genomes of Saccharum spontaneum, sugarcane cultivar R570, sugarcane cultivar Xintaitang 22 (XTT22), and Nicotiana benthamiana, respectively. Phylogenetic tree analysis classified the TETs into nine distinct groups. Nine TET genes were cloned from XTT22 and designated ScTET2, ScTET8, ScTET13, ScTET23, ScTET34, ScTET55, ScTET67, ScTET78, and ScTET96. RT-qPCR demonstrated the differential expression of these genes following SCMV infection. Furthermore, subcellular localization assays revealed that they were mainly localized to the plasma membrane (PM), except for ScTET2 and ScTET8, which were localized in the cytoplasm and formed irregular spherical structures of different sizes. Yeast two-hybrid (Y2H), bimolecular fluorescent complementation, and luciferase complementation assays revealed extensive interactions between the ScTETs and SCMV-6K2, primarily in the PM. Y2H assays also showed that TETs of Arabidopsis and N. benthamiana extensively interacted with the 6K2 protein of turnip mosaic virus.DiscussionThis study reveals a potential mechanism by which potyviruses employ 6K2 to interact with TETs to establish infection in host plants, thus highlighting potential molecular targets for engineering sugarcane resistance against SCMV.